2011
DOI: 10.1128/aac.01426-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Resistance or Cross-Resistance to Nonnucleoside Reverse Transcriptase Inhibitors Currently under Development as Microbicides

Abstract: Microbicides based on nonnucleoside reverse transcriptase inhibitors (NNRTIs) are currently being developed to protect women from HIV acquisition through sexual contact. However, the large-scale introduction of these products raises two major concerns. First, when these microbicides are used by undiagnosed HIV-positive women, they could potentially select for viral resistance, which may compromise subsequent therapeutic options. Second, NNRTI-based microbicides that are inactive against NNRTI-resistant strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 81 publications
2
10
0
Order By: Relevance
“…The K101E, E138K, K103N/S, F227C, Y181C, and K101E/G190A substitutions con- ferred low-level resistance to DPV, whereas the L100I/V, M230L, K101E/K103N, and Y181C/G190A substitutions and the Y188L, K101P, Y181I/V, K101E/Y181C, and K103N/ Y181C substitutions were found to confer intermediate and high-level resistance, respectively. The DPV cross-resistance profile reported in our study is consistent with prior in vitro studies of DPV resistance selection and cross-resistance profiling (15)(16)(17). Additionally, Penrose et al recently reported that there was frequent cross-resistance to DPV in subtype C-infected individuals after first-line therapy failure and reported that the L100I and K103N substitutions were significantly more frequent in samples with Ͼ500-fold resistance to DPV compared to samples with Յ500-fold resistance (18).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The K101E, E138K, K103N/S, F227C, Y181C, and K101E/G190A substitutions con- ferred low-level resistance to DPV, whereas the L100I/V, M230L, K101E/K103N, and Y181C/G190A substitutions and the Y188L, K101P, Y181I/V, K101E/Y181C, and K103N/ Y181C substitutions were found to confer intermediate and high-level resistance, respectively. The DPV cross-resistance profile reported in our study is consistent with prior in vitro studies of DPV resistance selection and cross-resistance profiling (15)(16)(17). Additionally, Penrose et al recently reported that there was frequent cross-resistance to DPV in subtype C-infected individuals after first-line therapy failure and reported that the L100I and K103N substitutions were significantly more frequent in samples with Ͼ500-fold resistance to DPV compared to samples with Յ500-fold resistance (18).…”
supporting
confidence: 80%
“…To our knowledge, this is the first study to define in detail the crossresistance profile for MIV-150, although one prior study identified different combinations of E138K, Y181I, Y181C, K103N, L100I, or K101E in simian immunodeficiency viruses expressing HIV reverse transcriptase (SHIV-RT viruses) exposed to MIV-150 in rhesus macaques, although no phenotypic data were provided (19). Additionally, prior studies have reported on the resistance profiles of the MIV-150 analogs, namely, MIV-160 and MIV-170 (16,17). Recently, we reported that an E138A substitution occurs more frequently in subtype C sequences (range, 5.9 to 7.5%) than subtype B sequences (range, 0 to 2.3%) from treatment-naive individuals (P Ͻ 0.01) (11).…”
mentioning
confidence: 99%
“…Results from a recent clinical trial delivering tenofovir using a gel based on hydroxyethylcellulose (HEC) have yielded especially encouraging results, as HIV acquisition was reduced by an estimated 39% 9 . A major concern with the large scale use of reverse transcriptase inhibitors (RTIs) is that if these agents are simultaneous used in HIV therapy there is the potential for the development of resistant strains 6, 7, 12 . Use of these therapeutics in undiagnosed HIV-positive women, could potentially promote the selection for resistant viruses 57, 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A major concern with the large scale use of reverse transcriptase inhibitors (RTIs) is that if these agents are simultaneous used in HIV therapy there is the potential for the development of resistant strains 6, 7, 12 . Use of these therapeutics in undiagnosed HIV-positive women, could potentially promote the selection for resistant viruses 57, 12 . Of additional significance is the increasing prevalence of viruses resistant to classes of antiretrovirals widely used in a community 13 .…”
Section: Introductionmentioning
confidence: 99%
“…One concern of small molecule drugs though, is the propensity for the development of resistant HIV strains. 1417 Macromolecular co-receptor inhibitors, by contrast, require HIV to undergo more difficult and arduous evolutionary paths to either utilize the original receptor in a new way or to switch tropism, particularly in going from R5 to X4 receptor usage. 18,19 The development of macromolecular inhibitors of these co-receptors, such as peptides and proteins, presents a potentially innovative means to develop new anti-HIV compounds.…”
Section: Introductionmentioning
confidence: 99%